URBAN VS. RURAL SOCIAL STRUCTURES IN INDIA: A COMPARATIVE STUDY - Ganapathi H B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to underscore the importance of inclusive policies and interventions to bridge the divide and promote equitable growth across urban and rural India. India, with its vast and diverse population, presents a striking contrast between urban and rural social structures, shaped by different economic, cultural, and social dynamics. This comparative study explores the key differences between urban and rural social systems in India, focusing on factors such as family structures, occupations, caste dynamics, education, and governance. Rural India, with its predominantly agrarian economy, is deeply influenced by traditional values, caste hierarchies, and close-knit community life. The family unit in rural areas is typically extended, and social interactions are heavily based on kinship, caste, and religious affiliations. Economic activities revolve around agriculture, with limited access to education, healthcare, and infrastructural development. In contrast, urban areas represent modernization, offering a more diverse and individualistic social structure. The rise of nuclear families, the breakdown of traditional caste structures, and greater access to education, healthcare, and employment opportunities mark the urban landscape. Cities are characterized by diverse cultures, greater economic opportunities in sectors like industry and services, and a more secular outlook, although caste-based discrimination persists subtly. Furthermore, urban areas benefit from more advanced governance systems, technological access, and better civic infrastructure, while rural India continues to face challenges related to poverty, limited opportunities, and slow-paced development. The study highlights the importance of understanding the evolving relationships between these two contrasting social structures, as rural-urban migration, technological advancements, and government interventions shape the socio-economic landscape of modern India. By analyzing the interdependence and challenges within both settings, this comparative study offers valuable insights into the complex dynamics that define contemporary Indian society.